A Study on Biochemical Parametrs in Patients with Rickettsial Infection (Academia Journal of Medicine, 2019)
Background: The traditional views of tick-borne rickettsioses as endemic diseases with largely focal distributions and limited host and  geographic ranges, predetermined seasonality and defined tick associations became obsolete or at least very incomplete. This expansion of  awareness about the existence of other rickettsial agents with varied clinical and epidemiological attributes has been thoroughly reviewed but it  has presented new challenges to the medical and public health communities. Subjects and Methods: The clinical presentation and multiple  organ dysfunctions in these patients were evaluated with a special focus on the renal manifestation and hepatic manifestations. The study  population included all the patients presenting fever, rash and were diagnosed with rickettsial disease by clinical examination. A total of 60  subjects, satisfying the inclusion and exclusion criteria were included in the final analysis. The sample size was calculated assuming the  expected proportion of rickettsial infection as 11% among fever cases as per previously published studies, with a precision of 8% and 95%  confidence level. Results: The mean AST in the 80 titre was 140.43 ± 79.92, it was 285.89 ± 184.95 in 160 titre, 364.92 ± 89.69 in 320 titre  group and 579.29 ± 106.26 in 640 titre group. The mean difference of AST 145.47 in 160 titre group was statistically significant (p  value
Keywords: Rickettsioses; Weil Felix Titre; Biochemical Parameters